1999
DOI: 10.1007/bf02463965
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies on new or critical fungi of non-pathogenic Onygenales 1

Abstract: From recent isolates of microfungi on soil materials collected at several localities in the world, five new taxa of the Onygenales are described and illustrated. A new monotypic genus, Kraurogymnocarpa lenticulospora, is proposed. New species are described in Amauroascus, Aphanoascus, and Arachnomyces. A new variety of Pseudogymnoascus roseus is also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, the new variety Pseudogymnoascus roseus var. ornatus (Udagawa and Uchiyama, 1999) has ascospores very similar in ornamentation to those of G.…”
Section: Discussionmentioning
confidence: 95%
“…However, the new variety Pseudogymnoascus roseus var. ornatus (Udagawa and Uchiyama, 1999) has ascospores very similar in ornamentation to those of G.…”
Section: Discussionmentioning
confidence: 95%
“…Pd is confirmed in seven North American [1, 4] and 13 European species of bats [4, 9]. The natural history of the genus Pseudogymnoascus and its allies indicate that they are commonly isolated from soils in colder regions of the world [16]. Unlike Pd many of its close relatives are cellulolytic saprobes and non-pathogenic [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a scanning electron microscope (SEM) study on ascospores of this fungus, Udagawa (1997) showed the ascospores to have bivalvate bodies which are ornamented with two widely separated equatorial crests and lobate-tuberculate surfaces. However, further examination of this fungus during our current study and detailed comparison with Kraurogymnocarpa lenticulospora Udagawa et Uchiyama, which had been described as the type species of new genus in 1999 (Udagawa and Uchiyama, 1999a), led us to re-evaluate its assignment in the Onygenales. However, further examination of this fungus during our current study and detailed comparison with Kraurogymnocarpa lenticulospora Udagawa et Uchiyama, which had been described as the type species of new genus in 1999 (Udagawa and Uchiyama, 1999a), led us to re-evaluate its assignment in the Onygenales.…”
Section: Taxonomymentioning
confidence: 79%
“…Note: After the publication of our first report in the series of taxonomic studies on new or critical fungi of non-pathogenic Onygenales (Udagawa and Uchiyama, 1999a), we became aware of the description of U. orissi by Sigler et al (1998by Sigler et al ( , published in 1999. Our new fungus, A. boninensis, is particularly similar to U. orissi.…”
Section: Chrysosporium-likementioning
confidence: 99%
See 1 more Smart Citation